IMPLEMENTATION OF PARTITIONING AROUND METHOD (PAM) IN IDENTIFYING THE CHARACTERISTICS OF NTT PROVINCE'S GNP - Chrisinta, Debora; Simarmata, Justin Eduardo (JURNAL DIFERENSIAL, 2024)
For the aspect of economic growth in NTT Province, it is necessary to understand regional characteristics in order to know the potential of each region. The aims of this study were to found the potential of regions in NTT that can increase the rate of economic growth by applying cluster analysis, namely the Partitioning Around Method (PAM). The data used is based on data from BPS with variables of GDP, Labor Force, Unemployment, Average Length of Schooling and Investment in 2022. The results showed that optimal clusters were obtained as many as 2 groups. Cluster 2 shows a larger average value than cluster 1. This means that districts/cities that tend to have higher GDP potential as well as labor force, unemployment, average length of schooling and investment are contained in cluster 2. Meanwhile, districts/cities in cluster 1 show a lower average.